The quality of spotted buffalo epididymal sperm with addition of raffinose as external cryoprotectant - Yulnawati .; Herdis .; H Maheshwari; M Rizal (Indonesian Center for Animal Research and Development (ICARD), 2008)
The aims of this research was to obtain the quality of Spotted buffalo epididymal sperm in different kind of extender in the three stages of cryopreservation (after dilution, post equilibration and post thawing). Spermatozoa was collected with combination of slicing and pressure method into the epididymal tissue in Andromedâextender. Soon after diluted and equilibrated, epididymal spermatozoa was cryopreserved in liquid nitrogen (-196°C). The result showed that the percentage of motility after thawing in Andromedâ + raffinose 0.4% (47.0 ± 2.4%), was significantly different (P<0.05) from that of control (41.0 ± 2.0%), but there was no significantly different (P>0.05) from that of Andromedâ + raffinose 0.2% (46.0 ± 2.0%). The percentage of live sperm after thawing in control (52.2 ± 2.5%), was the lowest and significantly different (P<0.05) from that of Andromedâ + raffinose 0.2% (59.2 ± 2.6%) and Andromedâ + raffinose 0.4% (58.8 ± 3.1%). Moreover, the percentage of membrane integrity after thawing in control, Andromedâ + raffinose 0.2% and Andromedâ + raffinose 0.4% was 68.0 ± 1.1%; 67.2 ± 1.6% and 67.6 ± 1.2%, respectively. There was no significantly different (P>0.05) in the percentage of membrane integrity from all treatments. In conclusion, the addition of 0.2 and 0.4% raffinose into Andromedâ extender could improve the percentage of motility and viability of post thawing spotted buffalo epididymal spermatozoa. Key Words: Epididymal Sperm, Cryopreservation, Raffinose, Spotted Buffalo